ANALISIS KURANGNYA PENGETAHUAN MATERI DALAM PEMBELAJARAN PENJUMLAHAN PECAHAN DI SISWA SMP OIKUMENE : ANALYSIS OF THE DIFFICULTIES OF GRADE 2 STUDENTS OF OIKUMENE MIDDLE SCHOOL, SORONG CITY IN UNDERSTANDING THE CONCEPT OF DIVISION OF FRACTIONS - Sundari; Zaenal, Reza Muhamad; lingasere, rosa delima; Falni; Runfaan, Alowesia Rosalina (KAMBIK: Journal of Mathematics Education, 2025)
Understanding the concept of fraction division is a basic skill that is important for second-grade junior high school students to master. This study aims to describe the level of students' understanding of the concept of fraction division. This study used a descriptive qualitative approach with data collection techniques through observation and interviews with six second-grade students of Oikumene Junior High School. The results showed that most students did not understand the basic concept of fraction division, including the inverse procedure in division operations and the identification of numerators and denominators. Although some students claimed to understand the terms numerator and denominator, they were unable to show them correctly in the form of a given fraction. The conclusion of this study shows that a weak understanding of the basic concept of fractions is one of the main causes of students' difficulties in solving fraction division problems, so a more contextual and conceptually oriented learning approach is needed.